Blockchain technologies as enablers of supply chain mapping for sustainable supply chains. (22nd March 2022) - Khan, Sharfuddin Ahmed; Mubarik, Muhammad Shujaat; Kusi‐Sarpong, Simonov; Gupta, Himanshu; Zaman, Syed Imran; Mubarik, Mobashar
Abstract: The advent of blockchain technologies is transmuting the way conventional supply chains are being managed. Due to the complexity of dealing with many actors involved in the supply chain networks, contemporary supply chains have limited visibility, transparency, and accountability. Likewise, supply chains are increasingly facing the challenge of integration and sustainability. In this vein, blockchain technologies can play a groundbreaking role in improving the traceability, accountability, and sustainability of complex supply chain networks. The present study examines the instrumentality of blockchain technologies in enabling supply chain mapping and supply chain integration. The study also tests the direct impact of blockchain technologies on supply chain sustainability. Data are collected from 132 Malaysian Electrical and Electronics firms using a close‐ended questionnaire. The study employs Partial Least Squares‐Structural Equation Modelling (PLS‐SEM) and Partial Least Squares‐Multi Group Analysis (PLS‐MGA) for analyzing the hypothesized relationships. The results show that blockchain technologies do not have a direct impact on supply chain sustainability. Nevertheless, this finding reveals a robust indirect effect of BT, through SC integration and SC mapping, on the SC sustainability. The study's findings imply that the notion of the sustainable supply chain can be significantly attained by mapping upstream, midstream, and downstream supply chains. The well‐mapped supply chain can further improve supply chain sustainability. The findings of the study also suggest the adoption of blockchain technologies as a broad‐based strategy to attain multi‐tier goals, for example, supply chain mapping, sustainability, and integration.